(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
Achieving the concept of sustainability in its aspects (environmental, social, economic) is an important orientation during the design of buildings in general and mosques and Islamic centers in particular, since the Islamic faith calls for respect for the environment and man and the preservation of the economy, where the general problem was the increasing interest in achieving these axes in accordance with high-tech technologies. Losing the clarity of its identity as an Islamic architecture because sustainability solutions may have a profound impact on the overall shape of the mosque where it represented the particular problem of research, and the research problem was defined by Cognitive impairment in the impact of the concept of sustainability on the clarity of identity in Islamic centers. Because the importance of Islamic centers in the definition of the Islamic religion, especially in the West. The aim of the research is to reach the design and technical principles recommended to be used in the architecture of contemporary Islamic centers to serve the achievement of sustainability in all its aspects without covering the features of its identity as Islamic architecture.The hypothesis of research (high-tech solutions to achieve sustainability affects the clarity of the identity of Islamic centers). The research methodology adopted a conceptual framework of knowledge to address the definitions of the concepts of sustainability in architecture in general and the definition of mosques and the identity of Islamic architecture as well as analysis and devise sustainability solutions through examples of traditional and contemporary mosques, also criticism of previous studies that addressed these concepts of sustainability and the identity of mosque architecture ,and then build the theoretical framework and extract the main and secondary variables, and then the practical part, which addressed elected samples of Islamic centers (global and Arab) to reach the final conclusions and recommendations. The most important research reached is the possibility of using high-tech technologies to achieve sustainability in the construction of Islamic centers without blurring the features of its identity as Islamic architecture, and the need to emphasize the clarity of the Islamic identity of sustainable Islamic centers as a pride in the Islamic faith and the historical legacy of the ancient mosque architecture. Variables of its theoretical framework as design / technical criteria preferred to be taken into account in the design of contemporary sustainable Islamic centers characterized by the clarity of its Islamic identity.